Analysis Of Financial Performance At Perum Bulog Baubau Branch Office - levian; Husriah; Andriani Saputri (International Journal of Multidisciplinary Learners, 2024)
The financial performance of Perum BULOG is the subject of this study. Baubau Branch Office as assessed by financial ratio analysis from 2019 to 2023. This study aims to determine the financial performance of Perum BULOG Baubau Branch Office from 2019-2023. The Quantitative descriptive data analysis was used. Liquidity, solvency, activity, and profitability ratios were measured. The results showed that the average current liquidity ratio at 2019-2023 Based on the average TMS solvency for FY 2019-2023 of 184.34%, which increases every year due to low loan expenditure, the company has difficulty paying off current liabilities with its current assets, which is 24.37%, which can be said to be less than good. 2019-2023 of 192,61%, It can be said to be very With the increase every year, this condition must be maintained so that the use of company assets becomes more efficient and effective. However, based on the average profit of return on investment (ROI) in 2019-2023 of 43,64%, it can be said to be very good. Financial performance be conclouded that during 2019-2023 Perum BULOG Baubau Branch Office has a healthy or good and less healthy level of financial health.